ANALISIS DAN PERANCANGAN SISTEM INFORMASI KOPERASI SIMPAN PINJAM BERBASIS WEB PADA MTs NEGERI TALANG BAKUNG KOTA JAMBI - Wati, Herly Kusuma; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2017)
The management of a good information system produces ease in accessing information data for anorganization. For ease of accessing the information required integration between information systems, with theexistence of various computer information system it will facilitate and accelerate the process of management inthe field of business one form of business that requires the management of computer based information system isa cooperative effort. Data is still done manually. The objectives in the study are to analyze and study theproblems of savings and loan based cooperative information system on MTs Negeri Talang Bakung. Systemdesign in this research using UML tool (United Modelling Language) that is Use Case diagram, activitydiagram and class diagram. While in making prototype system using adobe dreamweaver and to designdatabase using MySQL. In this research produce prototype information system of web based savings and loancooperative at MTs Negeri Talang Bakung which can manage.